Trading secrets : 20 hard and fast rules to help you beat the stock market - Thompson, Simon (Pearson Education, 2012)
Simon Thompson has been Companies Editor of Investors Chronicle, the UK’s leading magazine for private investors, since August 2000 and a finance journalist with The Financial Group in London over 10 years. His weekly Companies column for the Investors Chronicle is read by 35,000 online and magazine subscribers every week and is one of the most read sections of the magazine. Simon has an excellent track record at market timing, including calling the top of the Dow Jones Industrial Average within four days of the index hitting an all-time high in July 2007. His bearish view of the stock market has proved spot on with the four index short trades recommended in his Companies column producing an average profit of 44 per cent in 2008. Simon also has an outstanding record at stockpicking. Between 2004 and 2007 he gave 67 stock and index recommendations in his companies column in the Investors Chronicle of which 90 per cent showed a profit and an average gain of 33 per cent. In 2005, Simon had a 100 per cent track record with all sixteen of his recommendations in his column that year recording a profit.